A Virtual Navigation Training Promotes the Remapping of Space in Allocentric Coordinates: Evidence From Behavioral and Neuroimaging Data - Sacco, Katiuscia; Ronga, Irene; Perna, Pasqualina; Cicerale, Alessandro; Del Fante, Elena; Sarasso, Pietro; Geminiani, Giuliano Carlo (Frontiers in Human Neuroscience, 2022)
Allocentric space representations demonstrated to be crucial to improve visuo-spatial skills, pivotal in every-day life activities and for the development and maintenance of other cognitive abilities, such as memory and reasoning. Here, we present a series of three different experiments: Experiment 1, Discovery sample (23 young male participants); Experiment 2, Neuroimaging and replicating sample (23 young male participants); and Experiment 3 (14 young male participants). In the experiments, we investigated whether virtual navigation stimulates the ability to form spatial allocentric representations. With this aim, we used a novel 3D videogame (MindTheCity!), focused on the navigation of a virtual town. We verified whether playing at MindTheCity! enhanced the performance on spatial representational tasks (pointing to a specific location in space) and on a spatial memory test (asking participant to remember the location of specific objects). Furthermore, to uncover the neural mechanisms underlying the observed effects, we performed a preliminary fMRI investigation before and after the training with MindTheCity!. Results show that our virtual training enhances the ability to form allocentric representations and spatial memory (Experiment 1). Experiments 2 and 3 confirmed the behavioral results of Experiment 1. Furthermore, our preliminary neuroimaging and behavioral results suggest that the training activates brain circuits involved in higher-order mechanisms of information encoding, triggering the activation of broader cognitive processes and reducing the working load on memory circuits (Experiments 2 and 3).